Mengatasi Tantangan dalam Manajemen Berbasis Sekolah: Perencanaan untuk Peningkatan Pembelajaran dan Pengelolaan Sumber Daya - Yahya Ilma WS; Dian Hidayati; ST Martaningsih (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2024)
This study aims to examine the planning for implementing School-Based Management (SBM) at SMP IT Muhammadiyah An Najah Jatinom, focusing on improving the quality of learning and human resource (HR) management. Ideally, SBM is designed to enhance students' academic and religious competence through participatory planning involving teachers, parents, and the local community. However, despite the formulation of the school's vision and mission, the school faces limited resources and budget, which impact the implementation of planned programs. This research employs a qualitative descriptive method, with data collected through interviews, observations, and documentation from relevant parties, such as the Principal, Vice Principal, and Teachers. Data analysis was conducted through triangulation to ensure the validity and accuracy of the information obtained. The research findings show that although SBM planning is well-structured, focusing on improving teacher competency through training and workshops and developing infrastructure that supports technology-based educational facilities, there are still deficiencies in coordination and supervision that need improvement for more optimal implementation. Overall, this research emphasizes that structured and participatory planning is essential to achieving SBM success and enhancing educational quality, although challenges in resource management must be addressed for optimal implementation.